Anthropogeomorphology of Bhagirathi-Hooghly river system in India - Das, Balai Chandra; Ghosh, Sandipan; Islam, Aznarul; Roy, Suvendu (Boca Raton, FL : CRC Press, 2021)
The Bhagirathi-Hooghly Basin in India is one of the most densely populated regions in the world and is undergoing rapid transformation of its natural landscape induced by human interventions, such as mushrooming of dams and barrages, deforestation, and urbanization. Human activities and interventions on basin landforms and the processes that shape those landforms have accelerated at an alarming rate. This book uses spatio-temporal analysis to understand the major anthropogenic signatures on land use and land cover changes and the impact these activities have on thelandforms and processes of the Bhagirathi-Hooghly River and its sub-basins. It answers the what, where, why, and how of the anthropogenic signatures involved. Recent case studies on the impact of anthropogenic signatures on fluvial forms and processes make this book a useful resource for students and researchers in the earth sciences, local governments, urban planners, and all concerned with rural developments. Features: Explores for the first time the new concept of anthropogeomorphology for the river basin--an emerging field Analyses the impact of anthropogenic activities, especially the construction of dams and reservoirs, and urbanization on major fluvial landscapes using advanced geospatial modelling techniques Investigates human interference in river systems, their effects on the dynamics of the river, and the livelihoods of the people residing along the river Addresses issues related to geology, geomorphology, geography, planning, land use, and land management areas Fills the need for data-driven governance and policy decisions for the future of urban-industrial growth in India.
OCLC-licensed vendor bibliographic record.
Keywords: Geomorphology -- India -- Hugli River; Nature -- Effect of human beings on -- India; Hugli River Watershed (India) -- History; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; SCIENCE / Earth Sciences / General; TECHNOLOGY / Environmental Engineering & Technology